THE EFFECT OF A COMBINATION OF SLOW DEEP BREATHING AND MUSIC THERAPY ON REDUCING BLOOD PRESSURE IN THE ELDERLY WITH HYPERTENSION: CASE REPORT - Hasnatri Aulia Anwari; Arif Setyo Upoyo; Nuriya Nuriya (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Introduction: Hypertension is an abnormal increase in blood pressure that can cause persistent symptoms in target organs. Uncontrolled hypertension can lead to complications such as heart disease, kidney failure, and stroke. Nonpharmacological therapies that can be done to reduce blood pressure are slow deep breathing and music therapy. Purpose: To determine the effect of a combination of slow deep breathing therapy and music therapy on lowering blood pressure in the elderly with hypertension. Methods: The research design used a case study method by providing slow deep breathing and music therapy interventions for 7 days to 2 case study subjects who experienced hypertension. Data collection using observation sheets and standard operating procedures (SOP) slow deep breathing and music therapy. Blood pressure measurement tools use a digital Sphygmomanometer and data analysis using descriptive analysis. Discussion: The implementation results showed that after the combination of slow deep breathing therapy and music therapy for 7 days there was a decrease in blood pressure in both case study subjects. The decrease in blood pressure in case study subject I on the first day after therapy was 198/103 mmHg and after 7 days of therapy it became 178/101 mmHg. In case study subject II, on the first day of intervention, blood pressure was 163/97 mmHg and after intervention for 7 days it became 152/95 mmHg. Conclusion: Combination therapy of slow deep breathing and music therapy can reduce blood pressure in elderly people suffering from hypertension.